Optimasi Pemanfaatan Aset Pemerintah sebagai Upaya Revitalisasi Kawasan Alun-Alun Kota Bandung - Suciyani, Wida Oktavia (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
One of the government’s efforts to encourage community activities in city centers is establishing supplementary buildings which are acknowledged as government asset. However, after the completion of construction such buildings are often left idle and unpreserved therefore creating a grim impression in the area. This study examined such condition in Bandung City’s Main Square (Alun-Alun), Indonesia. The government established the Grand Mosque, Square Garden, KAA Building and Palaguna Shopping Area around the square, however, Palaguna Shopping Area has been idle in recent years.This study examined the re-utilization of the Palaguna Shopping Area as an Icon of Bandung City in terms of its (1) direction for optimum development, and (2) development feasibility. This study explored information through field observation, review of planning documents, and interview with respondents including Bandung City Government, PD Jawi (asset operator/owner), and local merchants. The study found that the optimum direction of development for Palaguna Area is as a super-regional shopping center. This finding was supported by feasibility of its financial, physical, locational and legal aspects.